Biodegradation of Soybean Biodiesel Generates Toxic Metabolites in Soil - Cruz, Jaqueline Matos [UNESP]; Montagnolli, Renato Nallin; Bidoia, Ederio Dino [UNESP] (My University, 2020)
Biodiesel is a mixture of fatty acid methyl esters (FAME) from either vegetable oils or animal fats. Although biodiesel biodegrades faster than diesel fuel, the impacts of this biofuel in environment throughout its biodegradation process should be investigated. For this reason, the objective of the present study was to evaluate the microbial activity, the phytotoxicity, and the formation of metabolites during biodegradation of the contaminated soil with biodiesel. Microbial activity was evaluated using culture-dependent methods in soil samples artificially contaminated with biodiesel—followed by pH adjustments. The formation of metabolites during biodegradation was identified using gas chromatography coupled with mass spectrometry (GC/MS). Respirometric method was also applied to evaluate total microbial activity. Seeds of Cucumis sativus were sown in soil samples before and after biodegradation to expand our knowledge on the impacts of such metabolites in a eukaryotic test-organism. Culture-dependent assays successfully allowed the quantification of microorganisms during biodegradation. According to CO2 production, biodiesel initially acted as a biostimulation agent increasing microbial activity. Indigenous microbiota degraded biodiesel into smaller compounds such as pentane, free fatty acids, and methanol. Soil pH significantly dropped from 5.4 to 3.0 after 120 days of biodegradation as a result of high concentration of free fatty acids. These free fatty acids inhibited further microbial growth after biodegradation. It was proposed that correcting soil acidity during biodegradation would be enough to sustain microbial growth. However, pH decrease was just one of the factors that inhibited microbial growth and plant root development. It was proposed that biodegradation yielded toxic metabolites such as methanol. These metabolites contributed to impair the root elongation due to alcohol-specific properties to solubilize a wide variety of lipids within the seed. Therefore, the present study draws attention to metabolites from biodegradation of biodiesel and their potentially harmful environmental impacts. Biodegradation of biodiesel changes soil pH, as it generates metabolites that are phytotoxic, and reduces microbial counts (CFU g−1 dry soil).
Keywords: Ecotoxicological; Free fatty acids; Methanol; Microorganisms; Phytotoxicity; Seeds